ESAT-6 protein suppresses allograft rejection by inducing CD4+Foxp3+ regulatory T cells through IκBα/cRel pathway - Huang, Xiaofei; Zeng, Yuqun; Lin, Jingru; Liu, Huazhen; Liang, Chun-Ling; Chen, Yuchao; Qiu, Feifei; Bromberg, Jonathan S.; Dai, Zhenhua (Frontiers in Immunology, 2025)
BackgroundMaintenance immunosuppression is required for suppression of alloimmunity or allograft rejection. However, continuous use of immunosuppressants may lead to various side effects, necessitating the use of alternative immunosuppressive drugs. The early secreted antigenic target of 6 kDa (ESAT-6) is a virulence factor and immunoregulatory protein of mycobacterium tuberculosis (Mtb), which alters host immunity through dually regulating development or activation of various immune cells. ESAT-6 may be a potential alternative immunosuppressant that could be utilized to suppress allograft rejection although it remains unknown whether ESAT-6 actually regulates alloimmunity.MethodsIn this study, murine skin or heart allotransplantation was performed to determine the effects of ESAT-6 protein on allograft survival. Flow cytometric analyses were conducted to quantify CD4+Foxp3+ Tregs, while immunohistochemistry was carried out to observe allograft immunopathology. Western blotting was used to detect IĸBα/c-Rel signaling during Treg induction. Finally, CD4+CD25- conventional T cells were cultured to induce Tregs and their proliferation.ResultsHere we found that ESAT-6 significantly extended murine skin and heart allograft survival, alleviated CD3+ T cell infiltration and increased Foxp3+ Tregs in an allograft. ESAT-6 augmented the percentage of CD4+Foxp3+ Tregs, whereas it decreased the frequency of Th1 and CD4+/CD8+ effector T cells in spleen and lymph nodes (LNs) posttransplantation. ESAT-6 also induced CD4+Foxp3+ Tregs from CD4+CD25- T cells in vitro by activating IĸBα/c-Rel signaling pathway, whereas inhibition of c-Rel signaling blocked Treg induction. Moreover, it suppressed conventional CD4+CD25- T cell proliferation in vitro in the absence of antigen-presenting cells (APCs), with an increase in IL-10 and decrease in IFN-γ production. On the other hand, it did not significantly alter DC maturation after allotransplantation.ConclusionThus, ESAT-6 suppresses alloimmunity and inhibits allograft rejection by inducing CD4+Foxp3+ Tregs through IĸBα/c-Rel signaling pathway.